MENCIPTAKAN LINGKUNGAN BERETIKA DALAM TATA KELOLA PEMERINTAHAN DI INDONESIA - Sylvia Sylvia (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2009)
Issu Good governance is intensively conversed by since Indonesia knocked over a economic crisis of year 1998. Good Governance interpreted wide by various science area. Shortly good governance translated by as arranging good management in organizational life, going into society to have, business, and work along. In context of corruption eradication, good governance is often interpreted by as governance which is clear of praktik corruption, kolusi, and nepotism. Thereby apply to arrange the not bad management at one blow run the organizational activity is which have ethics